Photocatalytic oxidation of H2S in the gas phase over TiO2-coated glass fiber filter. Issue 22 (16th November 2016) - Brancher, Marlon; Franco, Davide; de Melo Lisboa, Henrique
ABSTRACT: To promote the photocatalytic oxidation (PCO) of hydrogen sulfide (H2 S) in the gas phase, TiO2 -coated glass fiber filters were packed in an annular photoreactor. Glass fibers coated with TiO2 thin films were characterized structurally and morphologically by field emission gun scanning electron microscopy (FEG-SEM), scanning electron microscopy (SEM) coupled with energy-dispersive X-ray spectroscopy (EDS) and X-ray diffractometry (XRD). Flow rate and H2 S inlet concentration were evaluated to determine the performance of the reactor. Removal efficiencies up to 99% were achieved for flow rate of 25 L h −1 (residence time of 121 s) and H2 S inlet concentration from 12 to 14 ppmv. The long-term experiment presented H2 S removal of 89% for 16 h. After 28 h of continuous use, H2 S degradation was observed at 64%, which suggests that the photocatalyst was losing activity due to deactivation. Moreover, the kinetics of the PCO of H2 S according to the Langmuir–Hinshelwood (L–H) approach along with the mass balance of a plug-flow reactor was modeled. The reaction constant (k) was calculated at approximately 10.5 μmol m −3 s −1 and the adsorption constant (K) of approximately 5263 m −3 mol with linearity (R2 ) of 0.98.